1992
DOI: 10.1111/j.1440-169x.1992.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Echinonectin, an Endogenous Lectin of the Sea Urchin Embryo

Abstract: Echinonectin (EN) is a galactose-binding lectin present in eggs and embryos of the sea urchin Lytechinus variegatus. Recent studies have suggested that EN is a hyaline layer protein that may function as a substrate adhesion molecule (SAM) during development. We have used monoclonal and affinitypurified polyclonal antibodies that specifically recognize this protein to determine its spatial and temporal expression during embryogenesis. EN is stored in granules or vesicles in the unfertilized egg. After fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Gratwohl et al [1991] have demonstrated that toposome, a protein destined for export to the hyaline layer, is localized to both cortical and yolk granules in the unfertilized egg. Fuhrman et al [1992] have found that another hyaline layer protein, echinonectin, is localized to membrane-bound vesicles in the unfertilized egg. Similarly, in both Xenopus [Outenreath et al, 1988] and C. elegans [Creutz et al, 1996], exported proteins have been found in yolk granule-like structures in the unfertilized egg.…”
Section: Discussionmentioning
confidence: 99%
“…Gratwohl et al [1991] have demonstrated that toposome, a protein destined for export to the hyaline layer, is localized to both cortical and yolk granules in the unfertilized egg. Fuhrman et al [1992] have found that another hyaline layer protein, echinonectin, is localized to membrane-bound vesicles in the unfertilized egg. Similarly, in both Xenopus [Outenreath et al, 1988] and C. elegans [Creutz et al, 1996], exported proteins have been found in yolk granule-like structures in the unfertilized egg.…”
Section: Discussionmentioning
confidence: 99%
“…8 An anti-Echinonectin mAb localizes the epitope on the basal side of hyalin and in the cytoplasmic, membrane-bound vesicles of all 3 blastomere descendants. 40 The protein structure contains a series of coagulation factor 5/8 repeats and discoidin-like lectin domains and bears similarity to the secreted proteins DEL-1 and lactadherin from angiogenic Figure 3. A Hyalin repeat (HYR) domain structure.…”
Section: Apical Laminamentioning
confidence: 99%
“…However very few lectins are reported in echinoderms in comparison with those of other marine invertebrates. These include a few lectins from sea urchin, a sialic acid binding lectin belonging to the heat shock protein family [19], endogenous echinonectin from Lytechinus variegates [20], Lectin from Asterina pectinifera [21] and evidence for the involvement of lectin in the complement homologous immune system [4]. Sea cucumbers are echinoderms inhabitating relatively shallow coastal areas experiencing little or no currents.…”
Section: Introductionmentioning
confidence: 99%